‘ABD AL-JABBAR’S DEFINITION OF KNOWLEDGE - Ibrahim, Mohd. Radhi (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
This article will analyze ‘Abd al-Jabbar’s view on the definition of knowledge. It will show that not only are ‘Abd al-Jabbar’s definitions of knowledge influenced by his theology, but that they were developed throughout his intellectual development. Some views of the late Mu‘tazilites on ‘Abd al-Jabbar’s definitions of knowledge will be highlighted.